2004
DOI: 10.1002/polb.20156
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the molecular architecture, crystallization capacity, and miscibility in poly(butylene terephthalate)/polycarbonate blends: A comparison with poly(ethylene terephthalate)/polycarbonate blends

Abstract: Poly(butylene terephthalate) (PBT)/polycarbonate (PC) samples, prepared via reactive blending in the presence of Ti-and Sm-based catalysts, resulted in block copolymers whose block length decreased as the mixing time increased. A single homogeneous amorphous phase occurred when the blocks had monomeric sequences shorter than 10 units. Otherwise, a crystalline phase of PBT developed. Also, in poly(ethylene terephthalate) (PET)/PC blends previously studied, the miscibility was strictly correlated with the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…The copolymers have wide Table 1. Analyzed PET-co-PC and PET-samples, code used in the previous works [27,28,30] indicating the catalyst and the mixing time in Brabender, the molecular weight (M n ) and molecular weight distribution (M w =M n ), the number of PET monomeric units (X n PET ) and the results of the thermal analysis performed by DSC in the cooling scan. These latter data refer to the curves shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copolymers have wide Table 1. Analyzed PET-co-PC and PET-samples, code used in the previous works [27,28,30] indicating the catalyst and the mixing time in Brabender, the molecular weight (M n ) and molecular weight distribution (M w =M n ), the number of PET monomeric units (X n PET ) and the results of the thermal analysis performed by DSC in the cooling scan. These latter data refer to the curves shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[27] In particular, a single disordered phase is potentially present in the molten state, especially at short block length, while the presence of a mesophase-separated melt is unlikely. When these systems are cooled from the melt, two processes are in competition: block dissolution to form a homogeneous phase and phase separation by crystallization of PET and PBT blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the compatibility in polymer blends involve the preparative method of melt mixing (without use of a solvent) [3][4][5]7,8,[11][12][13][14][15][16][17][18][19][20][21]; rather few researches deal with solution blending (use of a solvent to dissolve the polymers) [2,6,22,23]. These studies commonly utilize analytical and conventional techniques [1][2][3][4][5][6][7][8][11][12][13][14][15]22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is worth noticing that the same basic pattern regarding both spacing and intensities was shared by all the copolymers revealing that the triclinic crystal structure of PBT was retained in the copolyesters. 36 Whereas it is thought that a length of at least 15-20 BT repeating-units is the minimum required for crystallization, 37 other observations have revealed that certain PBT copolymers are able to crystallize for chain segments consisting of only two to five repeating units. 38 A question immediately arises with respect to the location of the pentitol units in the biphasic semicrystalline state.…”
mentioning
confidence: 99%